Comparative analysis of accuracy between fine-needle aspiration biopsy and postoperative histopathology for detecting large thyroid nodules: A retrospective observational study - Zufry, Hendra; Nazaruddin, Nazaruddin; Zulfa, Putri O.; Sucipto, Krishna W.; Kamarlis, Reno K.; Ekadamayanti, Agustia S.; Beočanin, Anđelija; Firdausa, Sarah (Narra J, 2023)
To avoid unnecessary surgeries, ultrasound-guided fine-needle aspiration biopsy (FNAB) is an effective and reliable procedure for the preoperative evaluation of thyroid nodules. However, there have been only a limited number of studies exploring the ability of preoperative FNAB to distinguish malignancy compared to postoperative histopathology in thyroid nodules larger than 4 cm. The aim of this study was to investigate the diagnostic accuracy of FNAB compared to postoperative histopathology in distinguishing malignancy in thyroid nodules larger than 4 cm. A single-center retrospective observational study was conducted at Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia, between January 2014 and December 2018. The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were calculated. A total of 83 patients were included in the study. The results showed that preoperative FNAB may have the ability to distinguish malignancy compared to postoperative histopathology. The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were 42.85%, 98.38%, 90.00%, 83.56%, and 84.33%, respectively. These data suggested that ultrasound-guided preoperative FNAB is a reliable diagnostic tool in the preoperative evaluation of thyroid nodules larger than 4 cm, but it has limited capability in distinguishing malignancies. In conclusion, although FNAB may be useful in reducing unnecessary surgeries, histopathology remains the preferred method for confirming malignancy in thyroid nodules.